Research into safe traffic of Lithuanian railway lines - Černiauskaite, Laura; Podagelis, Igoris; Sakalauskas, Kazys (Transport, 2005)
The European Union directions pay a specific focus on traffic safety. Safety of railway transport traffic is among priority fields which has a direct effect on the quality of life of the population. It is most convenient to consider the number of breaks and accidents per year as the indicator of traffic safety. Reasons of traffic accidents can be very different. Most accidents occur due to poor technical condition of rolling‐stock and infrastructure, the human factor and the deficient organization of traffic. Stock Company “Lithuanian railways” can not assure safe traffic yet. The number of traffic incidents decreased in a few preserves only. Considering that, it is necessary to prepare a strategy for traffic safety and the program for its implementation. In 2002 specialists started preparing a study for safe traffic. The study is important for the preparation and implementation of the mentioned program. First results obtained from the research have already approved the importance of the influence of infrastructure, rolling‐stock and a human factor on traffic safety. The research carried out indicates positive changes in the situation of traffic safety of Lithuanian railways.First Published Online: 27 Oct 2010